Beam Switching in mmWave 5G: Evaluation in a Realistic Industrial Scenario - Antonio Tarrias; Sebastian B. Damsgaard; Melisa Lopez; Troels B. Sorensen; Preben E. Mogensen; Sergio Fortes; Raquel Barco (IEEE Access)
Fifth Generation (5G) Millimeter cellular networks are particularly interesting within the Industry 4.0 paradigm. mmWaves provide flexibility to the industrial use case, as well as enable specific application requirements, e.g. robots needing high data rates and low latency communication. Coverage at mmWaves, however, is challenged by additional attenuation and blocking effects, requiring the use of beamforming to overcome this by steering transmissions towards specific directions. Reliability is a key requirement as well, and requires, e.g, seamless beam switching during movement. Here, the resulting directivity of the antennas makes the beam switching procedures key to maintain the connectivity as the users move by. The present work aims to analyze the beam switching performance in a real-world indoor industrial scenario with high clutter to identify potential failures and propose optimization strategies. Firstly, this work has gathered insights into how beamforming operates under specific situations, identifying unused beams, relating the beam switching to the User Equipment (UE)’s movement, and collecting statistics from the beam switchings. Finally, a refined beam switching criteria is proposed based on radio metrics and location information, which outperforms the current criteria used by the network. This is evaluated based on the Reference Signal Received Power (RSRP) and the number of beam switchings under different criteria.